217k views
4 votes
Simplify (23)-2
- -13
2
ОО
O 64
DONE

Simplify (23)-2 - -13 2 ОО O 64 DONE-example-1
User Amin Eshaq
by
5.0k points

2 Answers

7 votes

Answer:

The correct answer choice is option b. 1/64

Explanation:

(2^3)^-2

= 2^3(^-2)

= 2^-6

= 1/2^6

= 1/64

User Sameer Azazi
by
6.0k points
3 votes

9514 1404 393

Answer:

(b) (correct choice is marked)

Explanation:

The expression can be evaluated according to the Order of Operations and the rules of exponents.

(2^3)^-2 = 8^-2 = 1/8^2 = 1/64

__

The applicable rule of exponents is ...

a^-b = 1/a^b

User Rene Chan
by
5.5k points